1984
DOI: 10.1021/jo00177a024
|View full text |Cite
|
Sign up to set email alerts
|

Acid catalysis of a linoleic acid hydroperoxide: formation of epoxides by an intramolecular cyclization of the hydroperoxide group

Abstract: Acid catalysis (0.1 M H2S04) of (13S)-(9Z,lLE)-13-hydroperoxy-9,ll-octadecadienoic acid (1) in methanol-water (9:1) did not afford appreciable yields of anticipated products, hexanal and (Z)-12-oxo-9-dodecenoic acid, via the known Hock rearrangement of hydroperoxides. Instead, intramolecular rearrangement of the 13-hydroperoxide into 12,13-epoxides, accompanied by solvent substitution, was the primary course of reaction (all products were isolated after conversion to methyl esters). Three isomeric methyl (Z)-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Consequently, the quantity of carbonyl compounds produced as a result of the acidic conditions (pH 3.0) used in our experiment, was taken into consideration by using a control trial containing all the components except the enzyme preparation. The results (unshown) indicated that the acid degradation of 13-HPODE did not produce appreciable yields of hexana1 42 ) in comparison to those obtained by enzymatic activity. Figure 6 shows the GC elution profile of the DNPHderivatized carbonyl compounds obtained by the F. proliferatum extract; the DNPH-derivatized carbonyl standards as well as those produced by the microbial extracts showed similar chromatograms.…”
Section: Carbonyl Compounds Formed By Hydroperoxide-cleaving Activitymentioning
confidence: 89%
“…Consequently, the quantity of carbonyl compounds produced as a result of the acidic conditions (pH 3.0) used in our experiment, was taken into consideration by using a control trial containing all the components except the enzyme preparation. The results (unshown) indicated that the acid degradation of 13-HPODE did not produce appreciable yields of hexana1 42 ) in comparison to those obtained by enzymatic activity. Figure 6 shows the GC elution profile of the DNPHderivatized carbonyl compounds obtained by the F. proliferatum extract; the DNPH-derivatized carbonyl standards as well as those produced by the microbial extracts showed similar chromatograms.…”
Section: Carbonyl Compounds Formed By Hydroperoxide-cleaving Activitymentioning
confidence: 89%
“…5) [23,24]. PCOOH has been reported to be easily decomposed by several factors, such as acids [35], metal ions [36], and temperature [37]. Thus, we spiked standard PCOOH (16:0/13-HpODE PC) into plasma and checked PCOOH recovery under different extraction conditions (Scheme 1).…”
Section: Discussionmentioning
confidence: 99%
“…and more recently picolinyl derivatives of fatty acids (21)(22)(23) were established to be useful for locating the double bond position and other structural modifications. Chemical ionization (CI) mass spectrometry has been tipplied to the study of unsaturated fatty acids esters (11) and epoxy (24,25) and hydroxy (25)(26)(27)(28)(29) substituted esters. The principal advantages of CI are enhanced molecular weight information and limited fragmentation, which makes key fragments more apparent.…”
mentioning
confidence: 99%